Development of Resilient and Smart Tourism Infrastructures: An Approach from Sustainable Engineering for High-Demand Tourist Areas - Franco Franco, Carmen Vanessa; Concha Diaz, Lady Shirley; Melgar Reynoso, Diana Carolina; Maceda Mogrovejo, Maria Alejandra; Cabana Mamani, Deyvin Herlin (Athenea Engineering sciences journal, 2025)
An integral proposal is presented for the development of resilient and smart tourism infrastructures in high-demand areas, based on the principles of sustainable engineering. Through a technical model involving structural, energy, and climatic simulations, the feasibility of implementing solutions that optimize operational performance, reduce environmental impacts, and strengthen adaptation to climate change is demonstrated. The results validate the multidimensional approach, highlighting its practical applicability, regulatory coherence, and potential for replication. It is concluded that the convergence between technology, sustainability, and social participation is key to transforming the tourism of the future.